ТАҲЛИЛИЙ ФИКРЛАШ ВА МУАММОЛИ ТАЪЛИМНИНГ ЎЗИГА ХОСЛИКЛАРИ - Мамбеткаримов, Р.Р. (SCIENCE and SOCIETY, 2022)
In this article, modern educational issues in the development of analytical thinking and problem-based education are comprehensively analyzed, showing the specific aspects of analytical thinking and problem-based education methods, and its main criteria.
Keywords: problem-based learning; problem-based task; intellectual; subject; state of mind; technology; method; model; philosophy. process; event